Copper-Copper Sulfate Reference Electrode for Operating in High Temperature and High Pressure Aqueous Environments. (10th December 2016) - Hall, Derek M.; Beck, Justin R.; Brand, Edward; Ziomek-Moroz, Margaret; Lvov, Serguei N.
Abstract: A copper-copper sulfate electrode (CSE) was constructed and tested at elevated temperatures. Experimental cell potentials versus a silver-silver chloride electrode were compared against results from Gibbs energy minimization (GEM) calculations. After accounting for irreversible thermodynamic processes, experimental and calculated CSE potentials, were generally within 3% of the observed potential from 25 to 150 °C at 3 MPa. The CSE potentials changed by less than 20 mV with increasing temperature, compared to 120 mV for the silver-silver chloride electrode. With its repeatability and small temperature dependence, the CSE electrode appears to be a viable reference electrode for measuring in-situ real time cell potentials in aqueous phase-containing media at elevated temperature and pressure.